Demonstration of high thermal performance GaN-on-graphite composite bonded substrate for application in III-V nitride electronics. (5th August 2021) - Li, Lei; Obata, Tomohiro; Fukui, Aozora; Takeuchi, Kai; Suga, Tadatomo; Tanaka, Atsushi; Wakejima, Akio
Abstract: Superior thermal performance of GaN/graphite composite (GC) bonded substrates having an ultralow thermal resistance ( R th ) has been demonstrated. Thermal transition in GaN-on-GC features fast relaxation process in GaN and slow case in GC, respectively. The temperature plateau at the GaN/GC interface indicates the R th across this interface is quite small and hence can be ignored. High-quality bonding interface and homogenous layer properties were obtained for the GaN-on-GC system. This favors the acoustic phonon transport and is bound to contribute to the outstanding thermal performance. The GaN/GC bonded substrate provides a promising candidate for thermal management applications in GaN-based electronics.